Intersubunit crosstalk in the Rag GTPase heterodimer enables mTORC1 to respond rapidly to amino acid availability - Shen, Kuang (Mol Cell, 2017)
mTORC1 is a central growth regulator that senses amino acids through a pathway that converges on the Rag GTPases, an obligate heterodimer of two related GTPases. Despite their central role in amino acid sensing, it is unknown why the Rag GTPases are heterodimeric and if their subunits communicate with each other. Here, we find that the binding of GTP to one subunit inhibits the binding and induces the hydrolysis of GTP by the other. This intersubunit communication pushes the Rag GTPases into either of two stable configurations, which represent active “on” or “off” states that interconvert via transient intermediates. Subunit coupling confers on the mTORC1 pathway its capacity to respond rapidly to the amino acid level. Thus, the dynamic response of mTORC1 requires intersubunit communication by the Rag GTPases, providing a rationale for why they exist as a dimer and revealing a distinct mode of control for a GTP-binding protein.